Interrogating sense of belonging and citizenship among Filipinos in diaspora in Taiwan - Agonos, Mariam Jayne M.
It is argued that the pervasive culture of migration among Filipinos is the main driver of the growth of the Filipino diaspora (Asis, 2017). Being part of a diaspora provides a space for migrants to reinvent their identity as they seek their own fortune and experience as sense of adventure in a different social setting. The continuity of Filipinos in diaspora may also suggests an "involuntary displacement from homeland" and subsequently, "alienation from host land" either of which evokes victimhood of the individual (Aguilar, 2015). the perspectives may indicate the spectrum of experiences of the Filipinos in diaspora in whichever country they may be. Acknowledging the different social realities, this study seeks to illustrate how Filipinos in diaspora negotiate sense of belonging and citizenship given the context of the host country. The study argues that Filipinos employ human agency alongside their respective social capital as they negotiate their sense of belonging and citizenship throughout their journey in Taiwan. Interviews from eight informants suggests that Filipinos in diaspora in Taiwan employ different strategies and may undergo different stages in achieving sense of belonging, which may be influenced not only by the community but the individuals themselves. Filipinos in diaspora seek that which is already familiar, thus, they often recreate social relationship in the host country by building relationships with kababayans, but they also try to create new networks with locals and other migrants. Moreover, while the sense of belonging can be characterized by the sense of being valued, trusted, and secured, it also involves the ability to be able to help others, contribute to a larger scale, or exceed the expectations presented to them. Meanwhile, legal citizenship is not something they actively pursue, rather, it is something that migrants may experience. Two emergent typologies of informal citizenship are manifested: latent which is more focused on thoughts and perspectives related to matters of the state, and demonstrated, which are the observable engagements and undertakings that benefit others. These manifestations of citizenship illustrate their current conditions and reflect their future plans, thus, while some of the informants display informal citizenship, the desire to acquire legal citizenship is either absent or not yet being considered. Furthermore, the experiences of the informants suggest that there is a relationship between sense of belonging and citizenship which merits further exploration. Findings of the study only characterize the living conditions of the informants as Filipinos in diaspora in Taiwan but not in other countries because per the narratives of the informants, Taiwan offers better benefits and living environment to its migrants in comparison to other labor-accepting countries. -- Provided by the author